Prozhektor perestroiki . Prozhektor perestroiki . The Perestroika Spotlight . Прожектор перестройки - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Exhibition of medical equipment with samples of surgical instruments from all over the world. Featured in the program: Axelrod, V.G. (Physician); Belenkov, IUrii Nikitich (Director of the Institute of Cardiology) Series description: Informational and analytical program, broadcasted in the Soviet Union in the late 1980's. The program was made during the “glasnost” period and was intended to describe and criticize the set of reforms. Выставка медицинской техники, где представлены образцы из разных стран мира. В программе участвуют: Аксельрод, В.Г. (Врач); Беленков, Юрий Никитич (Директор института кардиологии) Описание серии: Информационно-аналитическая телепередача в СССР конца 80-х годов. Передача была создана в период гласности для освещения и критики проводимых в стране реформ.